2021
DOI: 10.14207/ejsd.2021.v10n1p303
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Literature on Sustainability Reporting: A Bibliometric Analysis Grounded in Scopus and Web of Science Core Collection

Abstract: Sustainability reporting has become an increasingly common practice among companies around the globe as around 90% of the world’s 250 largest companies from Fortune 500 prepare and publish its sustainability reporting. Aiming to help researchers to grasp the intellectual landscape of global research on sustainable reporting, we conducted a bibliometric analysis using CiteSpace software by applying evaluative and relational techniques to 928 articles published in 480 different journals in Scopus and 698 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
(38 reference statements)
0
16
0
1
Order By: Relevance
“…The interest of companies on CSR actions are growing, and researchers [ 69 ] have identified 2011 as an important milestone in the maturity of sustainability reporting. Most research has investigated the degree of implementation of Directive by European companies and the quality of NFR and found that there are still many improvements to be made.…”
Section: Discussionmentioning
confidence: 99%
“…The interest of companies on CSR actions are growing, and researchers [ 69 ] have identified 2011 as an important milestone in the maturity of sustainability reporting. Most research has investigated the degree of implementation of Directive by European companies and the quality of NFR and found that there are still many improvements to be made.…”
Section: Discussionmentioning
confidence: 99%
“…2.1 Phase I: finding, assessing and screening studies A major step in any bibliometric data analysis is the choice of the database(s). While, at present, Scopus is the world's largest research database and covers more sources, the Web of Science core collection (WoS CC) is a reliable database that more academic researchers acknowledge for its high-quality publications (Pasko et al, 2021). However, there is a substantial content overlap between Scopus and WoS CC, which varies across disciplines.…”
Section: Review Methodsmentioning
confidence: 99%
“…A major step in any bibliometric data analysis is the choice of the database(s). While, at present, Scopus is the world's largest research database and covers more sources, the Web of Science core collection (WoS CC) is a reliable database that more academic researchers acknowledge for its high-quality publications (Pasko et al. , 2021).…”
Section: Review Methodsmentioning
confidence: 99%
“…ranking of 2019) now report on sustainability (KPMG, 2020, p. 10). Research-wise CSR also proliferates being a cluster trending upward in A* and A journals ranked according to the Australian Business Deans Council (ABDC) (Zengul et al, 2021;Pasko, Chen, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%